Indonesia Local Industry Structure and Firms Productivity in Industrial Area - Rinayanti Rinayanti; Riatu Mariatul Qibthiyyah (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2021)
Using three industry structure indices: specialization, diversification, and competition, we explore how local industry structure may affect firm productivity in the industrial estates. Based on unbalanced panel data of large and medium-sized industrial firms in Indonesia during 2010-2015, our study found that local industry structure influences firm productivity, measured as total factor productivity (TFP). The effect differs between firms outside the industrial estate and firms in the industrial estate. Specialization decreases the productivity of both firms in the industrial estate and outside. Diversification has a positive effect on increasing firm productivity in the industrial estate. As for firms outside the industrial estate, diversification has a negative effect, but the effect is less significant. Meanwhile, local industry competition has a positive and significant effect on firm productivity outside the industrial estate, but the effect is not significant for firms within the industrial estate. Empirically, firms in industrial estates may only benefit from a diversified local industry structure.JEL Classification: D24, L52, R10How to Cite:Rinayanti., & Qibthiyyah, R. M. (2021). Indonesia Local Industry Structure and Firms Productivity in Industrial Area. Signifikan: Jurnal Ilmu Ekonomi, 10(1), 93-112. doi: http://doi.org/10.15408/sjie.v10i1.17197.